Clinicohistologic Characteristics of Breast Cancer in Ghanaian Patients - Derkyi-Kwarteng, Leonard; F, Agyemang-Yeboah; L, Ahenkorah Fondjo; E, Gustav Imbeah; P, Kafui Akakpo (Annals of Pathology and Laboratory Medicine, 2020)
Background Breast cancer is the leading cause of cancer morbidity and mortality worldwide. The management and prognosis of breast cancer depend heavily on the different histologic and molecular biologic features of the tumour. The different histologic types describe the distinct growth patterns and cytological features of the tumour. Methodology This is a retrospective study of archival breast cancer excision and mastectomy specimen at KBTH from 2012-2016. 729 cases were retrieved over the period and examined by two pathologists independently. Demography of the cases, tumour size, grade, histologic type, stage, mitosis, site of lesion etc. were entered into SPSS and analysed with chi-square done with P-value set at P < 0.05. Results and Conclusion The mean age of presentation is 52.45 Â± 12.75 years. The commonest histologic type of breast cancer is invasive carcinoma (NOS) forming (87%). Only 1.2% of male presented with breast cancer with the other percentage in females. Most (88%) of the tumours were greater than 5cm at the time of surgery. The tumours are of high grade (II and III) forming 88%. Seventy-eight percent of cases presented with late stage of the disease (â‰¥ stage IIB). There was association between histologic type and vascular invasion (P < 0.000) and lymph node involvement (P = 0.010). Moreover, tumour size showed an association with tumour grade (P < 0.05). This study has shown that breast cancer among Ghanaian patients has a worse histologic type with poor tumour characteristics giving it poor prognosis.